Studi Komparasi Sistem Garansi Menurut Hukum Ekonomi Syariah dan Hukum Perdata - Siti Nuranisya; Fauzan Januri (SPT. haria Journal and Education Center Publishing, 2026)
This study aims to analyze the comparative system of warranty in Islamic Economic Law (specifically the concept of khiyār ‘aib) and the warranty system in Civil Law (KUHPerdata). The main focus of this study is to identify points of convergence, divergence, and the juridical implications of these two legal instruments in protecting consumers from defective products. The research method used is normative legal research with a comparative approach. The results indicate fundamental similarities regarding the buyer's right to rescind or proceed with the transaction if a defect is discovered, as well as the seller's obligation to be responsible for latent defects. However, there are significant differences in determining the warranty period and the criteria for claimable defects. In terms of juridical implications, these differences lie in the legal subjects, the scope of the objects, and the nature of the contracts used. The study concludes that although khiyār and warranty have different philosophical foundations, they share the same goal of ensuring justice and protection for parties involved in sales transactions.